2010
DOI: 10.1111/j.1523-5378.2010.00748.x
|View full text |Cite
|
Sign up to set email alerts
|

Ten‐Day Sequential Therapy as First‐line Treatment for Helicobacter pylori Infection in Korea: A Retrospective Study

Abstract: Ten-day sequential therapy is found to effectively eradicate H. pylori infection as first-line treatment in Korea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Adverse events were reported in 41 studies (24 RCTs and 17 observational studies) with 8,018 subjects treated with standard triple therapy (22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62). The incidence of adverse events in these studies was 20.4% (95% CI, 19.6%-21.3%).…”
Section: Resultsmentioning
confidence: 99%
“…Adverse events were reported in 41 studies (24 RCTs and 17 observational studies) with 8,018 subjects treated with standard triple therapy (22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62). The incidence of adverse events in these studies was 20.4% (95% CI, 19.6%-21.3%).…”
Section: Resultsmentioning
confidence: 99%
“…8,9 The fall in treatment success has led to the introduction of new regimens, such as a 10-day sequential therapy, 27-30 a 7-day non-bismuth-containing quadruple therapy (a PPI, amoxicillin, clarithromycin, and nitroimidazole), and a 14-day bismuthcontaining quadruple treatment (a PPI, bismuth, tetracycline and nitroimidazole). 33 However, a recent study by Choi et al reported that there were no differences in eradication rates between sequential therapy and 10-day standard triple therapy (78% vs 72%) in Korea. The therapeutic efficacy seems suboptimal for clinical use.…”
Section: Discussionmentioning
confidence: 96%
“…At present, the sequential therapy is one suggested alternative first‐line strategy: several pooled data studies and meta‐analyses have shown this treatment to yield better eradication efficacy than the traditional triple therapy . In Korea, a region with relatively high antibiotic resistance, the efficacy of sequential therapy has been reported in several randomized controlled trials including our previous prospective studies . These studies initially indicated the sequential therapy to be effective, but recent results have been less satisfactory.…”
Section: Introductionmentioning
confidence: 99%